Кооперативные деформационные процессы и локализация деформации - Лихачев В. А. Владимир Александрович; Панин В. Е. Виктор Евгеньевич; Засимчук Е. Э. Елена Эмилевна; Владимиров В. И.; Романов А. Е.; Немошкаленко В. В. Владимир Владимирович (Киев, Наукова думка, 1989)
Авт. указаны на обороте тит. листа